Connection topology of step edge state bands at the surface of a three dimensional topological insulator. (6th July 2018) - Xu, Yishuai; Jiang, Guodong; Chiu, Janet; Miao, Lin; Kotta, Erica; Zhang, Yutan; Biswas, Rudro R; Wray, L Andrew
Abstract: Topological insulators (TIs) in the Bi2 Se3 family manifest helical Dirac surface states that span the topologically ordered bulk band gap. Recent scanning tunneling microscopy measurements have discovered additional states in the bulk band gap of Bi2 Se3 and Bi2 Te3, localized at one-dimensional step edges. Here numerical simulations of a TI surface are used to explore the phenomenology of edge state formation at the single-quintuple layer step defects found ubiquitously on these materials. The modeled one-dimensional edge states are found to exhibit a stable topological connection to the two-dimensional surface state Dirac point.